How to lead OH & S risk management a guide for managers and supervisors - Nicholas and Smith (Firm) (Australia : Nicholas and Smith, 1998)
Video and guide is based on a typical workplace assessment, using real Australian case study examples. Merck Sharp & Dohme is a pharmaceutical manufacturer while AMP is a financial services organisation.
DVD format
Keywords: Industrial safety -- Australia -- Case studies; Accidents -- Australia -- Prevention